Facile phase transition engineering of MoS2 for electrochemical hydrogen evolution. Issue 13 (12th March 2021) - Gao, Bo; Zhao, Yiwei; Du, Xiaoye; Chen, Yaqi; Guan, Boyuan; Li, Yan; Li, Yanhuai; Ding, Shujiang; Zhao, Hongyang; Xiao, Chunhui; Song, Zhongxiao
Abstract : Magnetron sputtering and DFT calculations revealed that the single-doped Cu-MoS2, Au-MoS2, Ag-MoS2, and Al-MoS2 exhibited distinct phase transitions compared to Cr-MoS2, Hf-MoS2, Ta-MoS2, and Zr-MoS2, due to the introduction of additional charge. Abstract : Metallic phase molybdenum disulfides exhibit impressive charge transfer ability and this has made them interesting candidates for use in the field of nano-science and heterogeneous catalysis. However, the synthesis of 100% pure bare 1T-MoS2 is difficult due to its kinetic instability. In the past, the phase transition mechanism from a semiconductor (2H) to a metallic (1T) phase has been explained only by theoretical calculations. Herein, we used magnetron sputtering to deposit a series of MoS2 films containing various metal heteroatoms as the dopants. Density functional theory (DFT) calculations revealed that the single-doped Cu-MoS2, Au-MoS2, Ag-MoS2, and Al-MoS2 exhibited distinct phase transitions compared to Cr-MoS2, Hf-MoS2, Ta-MoS2, and Zr-MoS2, due to the introduction of additional charge. Furthermore, the hydrogen evolution reaction (HER) activities of the series of MoS2 films were explored, and the adsorption free energy of H atoms was evaluated by DFT calculations.